LEADS SEARCH FOR ACETYLCHOLINESTERASE INHIBITORS DERIVED FROM SECONDARY METABOLITES OF ENDOPHYTIC FUNGI: A REVIEW - Putra, Pramana Kumala; Dewi, I Gusti Ayu Agung Gangga Samala; Putri, Ni Wayan Prasanthi Swarna; Wirajana, I Nengah; Ariantari, Ni Putu (Journal Pharmaceutical Science and Application, 2024)
Background: Acetylcholinesterase inhibitors (AChEIs) are substances that act by increasing acetylcholine levels in the brain to prevent neurotransmitter degradation. AChEIs are the most widely used agents for Alzheimer's disease (AD) therapy so far. Objective: This study aims to give insight into AChEIs produced by endophytic fungi through literature reviews, which are promising for further studies on their mode of action. Methods: Data search was conducted through scientific-based websites such as Google Scholar, Science Direct, and PubMed, which involved scientific publications from January 2000 to December 2022. Results: Fifteen genera, including Aspergillus, Cladosporium, Colletotrichum, and Penicillium, were reported to produce twenty-four secondary metabolites with AChEI activity. These compounds were classified based on their chemical skeleton into alkaloids, steroids, terpenoids, polyketides, and peptides. Conclusion: Endophytic fungi are promising sources of lead compounds possessing AChE inhibitory activity. Further research on molecular mechanisms of secondary metabolites from endophytic fungi with AChEI activity can provide new insight into the development of more potent AChEIs for AD treatment. Keywords: Acetylcholinesterase inhibitors (AChEIs); Alzheimer’s disease; endophytic fungi; secondary metabolites.